Angiotensin II and taste sensitivity. Issue 2 (May 2015) - Shigemura, Noriatsu
Summary: The sense of taste plays a major role in evaluating the quality of food components in the oral cavity. Sweet, salty, umami, sour and bitter taste are generally accepted as five basic taste qualities. Among them, salty taste is attractive to animals and influences sodium intake. Angiotensin II (ANG II) and aldosterone (ALDO, which is stimulated by ANG II) are key hormones that regulate sodium homeostasis and water balance. At the peripheral gustatory organs, it has been reported that ALDO increases the amiloride-sensitivity of the rat gustatory neural responses to NaCl in a time course of several hours. A recent study demonstrated that ANG II suppresses amiloride-sensitivity of the mouse gustatory and behavioral responses to NaCl via its receptor AT1 within an hour. Moreover, ANG II enhances sweet taste sensitivity without affecting umami, sour and bitter tastes. These results suggest that the reciprocal and sequential regulatory mechanisms by ANG II (as an acute suppressor) together with ALDO (as a slow enhancer) on the salt taste sensitivity may exist in peripheral taste organs, contribute to salt intake, and play an important role in sodium homeostasis. Furthermore, the linkage between salty and sweet taste modulations via the ANG II signaling may optimize sodium and calorie intakes.